Catalpol Protects Against High Glucose-Induced Bone Loss by Regulating Osteoblast Function - Lu Zhao; Wei Du; Dandan Zhao; Xueyan Ji; Yanfei Huang; Yong Pang; Kaijin Guo; Xiaoxing Yin (Frontiers Media S.A., 2021)
Objective: The overall objective of this study was to investigate the effects of catalpol on bone remodeling of diabetic osteoporosis by regulating osteoblast differentiation and migration.Method: Using a murine model of diabetic osteoporosis, to detect the protective effects of catalpol on bone loss, architectural deterioration of trabecular bone and bone metabolism biomarkers were tested. A model of MC3T3-E1 cells was established by treatment with high glucose; the regulatory role of catalpol in the differentiation and migration was tested by Western blot, ALP staining, and Alizarin Red staining.Results: Catalpol treatment markedly ameliorated trabecular bone deterioration by reducing degenerative changes of the trabecular structure by improving the bone formation marker levels of ALP, osteopontin, type I collagen, and osteocalcin, as well as the level of OPG/RANKL. Catalpol enhanced cell motility and scattering following gap formation of MC3T3-E1 cells.Conclusion: The results indicated that catalpol exhibits a protective effect against diabetic osteoporosis by regulating the differentiation and migration of osteoblast.